The Influence of Instructional Media E-Learning Based Edmodo on Student Learning Outcomes of Basics Banking Class X Accounting - Monica Dewi; Sri Zulaihati; Achmad Fauzi (International Journal on Advanced Science, Education, and Religion, 2021)
This study aims to determine the effect of Edmodo-based e-learning media on student learning outcomes in the subjects of banking basics class X Accounting at SMK Negeri 42 Jakarta. The research method used is a quasi-experimental method with a research design post-test only control design. The samples taken were class X Accounting 2 as the experimental class and X Accounting 1 as the control class with 36 students each. The instrument used is a test. The test results data were analyzed by normality test, homogeneity test and hypothesis testing. The results of the normality test showed that the experimental class obtained Lcount (0.113) < Ltable (0.147) this means the data is normally distributed and in the control class obtained Lcount (0.101) < Ltable (0.147) this means the data is normally distributed. The homogeneity test shows that Fcount (1.22) < Ftable (1.76) then the data used is homogeneous. The results of hypothesis testing state that tcount (13.79) < ttable (1.66) this means that there is an influence of Edmodo-based e-learning learning media on the learning outcomes of students of class X accounting expertise competence at SMK Negeri 42 Jakarta Keywords: Learning Media, Learning Edmodo, Instructional Media E-Learning